European Film and Television Co-production Policy and Practice (Palgrave European Film and Media Studies, 2018)
This volume offers an up-to-date analysis of film and television co-production in Europe. It brings together the voices of policy professionals, industry practitioners and media industry scholars to trace the contours of a complex practice that is of increasing significance in the global media landscape. Analysis of the latest production statistics sits alongside interviews with producers and the critical evaluation of public film policies. The volume incorporates contributions from representatives of major public institutions-Eurimages, the European Audiovisual Observatory and the European Commission-and private production companies including the pan-European Zentropa Group. Policy issues are elucidated through case studies including the Oscar-winning feature film Ida, the BAFTA-winning I am not a Witch and the Danish television serial Ride Upon the Storm. Scholarly articles span co-development, co-distribution and regional cinemas as well as emerging policy challenges such as the digital single market. The combination of qualitative and quantitative approaches, and the juxtaposition of industry and scholarly voices, provides a unique perspective on European co-production that is information-rich, complex and stimulating, making this volume a valuable companion for students, scholars, and industry professionals.